Development of the Student Worksheets Based on Assessment for Learning (AfL) to Improve Student Learning Outcomes of the Elements Periodic Table - Galang Firman Syah; Muchlis (Postgraduate, University of Mataram, 2025)
This study aims to develop student worksheets based on assessment for learning to improve student learning outcomes on the elements periodic table, focusing on enhancing students' conceptual understanding. The study uses a 3D development model modified from the 4D model, consisting of three steps: define, design, and develop, applied to class X-7 at a school in Surabaya. Instruments for assessing validity include expert reviews of material and design, with a median score of ≥ 4, indicating content and construct validity. Practicality is measured through student response questionnaires and activity observations, with a positive response mode of ≥ 61%. The worksheet’s effectiveness is evaluated through the achievement of learning objectives, with an N-gain value showing 1 student (2.86%) in the medium category and 34 students (97.14%) in the high category. Posttest results show > 75% of students exceeding the passing grade. The Wilcoxon Signed Rank test shows a Pvalue < 0.05, indicating a significant difference in student learning outcomes. Based on these findings, the developed worksheet is deemed valid, practical, and effective in improving student learning outcomes.